The installation of water reticulation pipe system in Universiti Sultan Zainal Abidin, Kuala Terengganu / Nur Liyana Kamarudin - Kamarudin, Nur Liyana (Universiti Teknologi Mara, Perak, 2018)
Water reticulation system for university is the same like other building. It involves component such as distribution, pressure and pump system. The pipe in water reticulation system are used as network for distribution of water to the consumers. The pipe elements are involving components such as elbows, flanges, reducers, tees, expansion bellows and else. Due to the long duration of usage of 38 years, Universiti Sultan Zainal Abidin (UniSZA) intends to reinstall new types of pipe, from the Asbestos-Cement Pipe to Multi Polyvinyl Chloride pipe (MPVC pipe) for the comfort of UniSZA occupants. This report will elaborate in detail on the installation of the new pipe system.